Halal Tourism: The Development of Sharia Tourism in Baturraden Banyumas, Indonesia - Syufa'at, Syufa'at; Zayyadi, Ahmad (Indonesian Academy of Social and Religious Research (IASRR), 2023)
This research is motivated by the DSN-MUI Fatwa Number 108/DSN-MUI/X/2016 as the basis for the concept of halal tourism in the trend of sharia tourism management models, sharia tourism development in Baturraden Banyumas. The research method used in this study is the constructivist paradigm used to see the phenomenon of community behavior around tourist sites. The results showed that the tourism potential in Baturraden Banyumas to be developed into sharia tourism. First, the public can understand the meaning of sharia tourism, tourism is carried out for recreational purposes in accordance with the concept of halal tourism in the DSN - MUI fatwa. Second, tourism activities and tourist sites are sufficiently protected from immoral activities, only a few things need to be improved, namely the application of the rules of no dating and the implementation of a stricter curfew. Third, tourist sites are quite comfortable and safe. Fourth, in tourist sites there are many facilities for places of worship, restaurants, souvenir shops.